Hegemonic Wellness: A Post-Covid Assault on Teachers and Teaching - Saul, Roger (Radical Teacher, 2023)
This essay considers the meanings, operations, and effects on educational life of hegemonic wellness, a term the author coins to capture a recurring discourse emerging from his recent seminar work with a group of graduate students. Hegemonic wellness refers to a developing school movement aimed at positioning neo-liberal ‘wellness’ discourses as the most socially valued means of making sense of an educator’s workplace health. It constructs notions of healing and care as radically individualist pursuits, deeply anti-communitarian in theory and practice, and best positioned to serve existing power structures rather than to contest them. In naming and contesting hegemonic wellness, the author expects that teachers may find a language of recognition, affirmation, and contestation that can come to bear upon their practices.